Activities and participation of 65-91-year-old adults: population-based study among residents of a sparsely populated and remote area in Iceland. Issue 1 (1st January 2021) - Brynjolfsdottir, Margret; Palmadottir, Gudrun; Arnadottir, Solveig A.
ABSTRACT: Southern Westfjords of Iceland is a sparsely populated, remote area with rather high proportion of older residents. This study´s aim was to investigate activities and participation in this population, using a descriptive cross-sectional population-based design. The participants were 129 community-dwelling residents, 65–91 years old. The Late Life Function and Disability Instrument was used to measure participants' activities and participation. It provides interval scale scores where a higher score means less difficulties in activities, more frequent participation, and fewer participation restrictions. Participants had most difficulties in Advanced Lower Extremity functioning and least in Upper Extremity functioning and scored lower on participation frequency than participation restriction. Overall, men reported fewer difficulties in activities than women and the 65–74 years group fewer difficulties than the 75–91 years group. Frequency of participation was higher for women than men and higher for the younger group than the older one who also experienced their participation to be more limited, but men and women did not differ. The participants described barriers limiting their participation in self-care and social life. The results provide valuable information on activities and participation of older residents living rurally and have practical implications for community services in remote arctic areas.